Increased Membrane-bound Adenosine Triphosphatase Activity Accompanying Development of Enhanced Solute Uptake in Washed Corn Root Tissue - Leonard, R. T. (1972)
Washing of excised corn (Zea mays L., variety WF9×M14) root tissue is accompanied by an increase in (Mg(2+) + K(+))-stimulated adenosine triphosphatase. This is the adenosine triphosphatase described by Fisher, Hansen, and Hodges as positively correlated with ion accumulation rates. The increase in activity is confined to the microsomal fraction. A close parallel exists between increases in adenosine triphosphatase and phosphate absorption, and they respond similarly to inhibitors of RNA and protein synthesis. However, the amplitude of change is much smaller in adenosine triphosphatase. Possible reasons for this discrepancy are discussed.